Monopsony, Buying Costs,and Welfare Expenditure - Rothschild, K. W. (Review of Economic Studies, 1942)
Journal Article Monopsony, Buying Costs, and Welfare Expenditure Get access K. W. Rothschild K. W. Rothschild Glasgow Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 10, Issue 1, Winter 1942, Pages 62–67, https://doi.org/10.2307/2967496 Published: 01 December 1942